Epigenetics in Esophageal Cancer: From Mechanisms to Therapeutics. Issue 10 (9th August 2020) - Liao, Long; Yao, Zi‐Ting; Fang, Wang‐Kai; He, Qing‐Yu; Xu, Wen Wen; Li, Bin
Abstract: Esophageal cancer is a leading cause of cancer‐related deaths worldwide. In the past few years, the roles of epigenetics in cancer have been fully accepted. Recently, there has been an increased focus on epigenetic alterations underlying esophageal cancer carcinogenesis, with several epigenetic drug and RNA interference therapies being tested. However, the conclusion that epigenetic alterations are linked directly to an increased or decreased risk of esophageal cancer is less certain. Therefore, there is an urgent need to test novel epigenetic biomarkers for diagnostic and prognostic significance and to explore their potential as therapeutic targets. In this review, the discussion is concentrated on epigenetic alterations involving super‐enhancers, DNA methylation, histone modifications, and multiple noncoding RNAs (ncRNAs), including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs), and their impact on tumor growth, invasion, metastasis, and drug resistance. Then specific instances of using epigenetic drugs, such as DNA methyltransferase and histone deacetylase inhibitors, to treat esophageal cancer are described. Recent developments in miRNA‐based therapeutic strategies, including antagomirs, lock nucleic acids, miRNA sponges, and microRNA replacement therapies, against esophageal cancer are also highlighted. Abstract : Esophageal cancer is a leading cause of cancer‐related deaths worldwide. Here it is aimed to offer an updated knowledge of epigenetics in esophageal cancer, including the roles of super‐enhancers, DNA methylation, protein post‐translational modifications (PTMs), and RNA disorders. Where relevant, existing and emerging drugs that target epigenetic factors in esophageal cancer are also highlighted.